2007
DOI: 10.1007/s10508-007-9233-9
|View full text |Cite
|
Sign up to set email alerts
|

Coping Styles as Mediator of Sexual Orientation-Related Health Differences

Abstract: The higher prevalence of health problems in homosexual compared to heterosexual populations is usually understood as a consequence of minority stress. We hypothesized that differential rates of health problems also could result from sexual orientation-related differences in coping styles. We explored this using data collected in a general population-based study (N = 9684) via face-to-face interviews. A higher prevalence of both mental and physical health problems, as assessed with individual questions, the GHQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…Because these disparities seem to be present at a young age [36, 37], a life course perspective should be adopted. This perspective should include the development of coping styles, given the mediating role of coping in the association between sexual orientation and mental health [38]. A life course perspective will also offer insights in optimal timing of interventions aimed at the prevention of mental health disparities related to sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Because these disparities seem to be present at a young age [36, 37], a life course perspective should be adopted. This perspective should include the development of coping styles, given the mediating role of coping in the association between sexual orientation and mental health [38]. A life course perspective will also offer insights in optimal timing of interventions aimed at the prevention of mental health disparities related to sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Although being part of a minority group per se is not a risk factor for psychological maladjustment (Koh and Ross 2006), feeling distressed about sexual orientation discrimination increases the odds of having a mental health problem (Koh and Ross 2006;Mays and Cochran 2001;Sandfort et al 2006Sandfort et al , 2009. Therefore, feelings and cognitions common among lesbian women due to their sexual orientation may have an important impact on their sexual interactions and sexual functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Sandfort, Bakker, Schellevis, and Vanwesenbeeck (2009) found that emotion-oriented and avoidance coping strategies were more strongly applied by homosexual men than by heterosexual men. For the women in this study, however, sexual orientation was not significantly related to coping styles.…”
Section: Introductionmentioning
confidence: 91%